2008
DOI: 10.1007/s11746-008-1276-0
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid, Tocopherol and Sterol Compositions of Canadian Prairie Fruit Seed Lipids

Abstract: The seeds of four prairie fruits-chokecherry (Prunus virginiana), thorny buffaloberry (Shepherdia argentea), Woods' rose (Rosa woodsii) and hawthorn (Crataegus 9 mordenensis)-from Southern Alberta were investigated. The lipid contents of the seeds were found to be 10.4, 11.5, 3.7 and 3.4%, respectively. The tested seed lipids contained mainly linoleic acid in the range from 27.9 to 65.6% and oleic acid from 19.7 to 61.9%. The thorny buffaloberry and Woods' rose seed lipids contained 29.2 and 30.8% of linolenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…Tocopherols were analyzed as previously described [12]. Briefly, 50 mg oil was weighed directly into a 1.5-mL vial and mixed with 1 mL hexane.…”
Section: Tocopherol Analysismentioning
confidence: 99%
“…Tocopherols were analyzed as previously described [12]. Briefly, 50 mg oil was weighed directly into a 1.5-mL vial and mixed with 1 mL hexane.…”
Section: Tocopherol Analysismentioning
confidence: 99%
“…In recent years, much attention has been focused on exploring different plants as alternative sources of functional compounds [1]. Recent epidemiological studies have suggested that increased consumption of whole grains, legumes, fruits, and vegetables is inversely associated with the risk of chronic diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of b-sitosterol as principal component in KSO is in line to those of several common vegetable oils which also contain this component as the major phytosterol [27]. Phytosterols are one of the important non-glyceridic minor components in vegetable oils that play beneficial role in reducing absorption of cholesterol and the amount of negative lipoproteins in human blood and thus can potentially reduce the incidence of cardiovascular diseases [24].…”
Section: Phytosterols Composition Of Oilmentioning
confidence: 79%
“…The phytosterols composition of the oil was studied following the method as described in one of our recent publications [24]. The oil was saponified with methanolic KOH and the unsaponifiable materials extracted with diethyl ether.…”
Section: Phytosterols Of Oilmentioning
confidence: 99%
See 1 more Smart Citation